2018
DOI: 10.5296/ijhrs.v8i3.13450
|View full text |Cite
|
Sign up to set email alerts
|

Public Private Partnership: Insights from the Egyptian Experience

Abstract: Partnership between private and public organizations has become very vital for policy implementation. PPP contracts have been successful for the recent years in many countries such as United Kingdom, Germany, Netherlands, South Africa, and The United States. Egypt is considered to be one of the MENA region leaders in the PPP field. PPPs are considered to be on the top of the Egyptian economic reform agenda so as to increase the private sector involvement in public services through leveraging private sector spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The study indicated that the extent and quality of voluntary information disclosed by the private construction companies was low. Samir and Maher (2018) analyzed the role of public private partnership in Egypt in terms of developing meaningful cooperation between the governments and private sector companies in a way that enables the provision of high-quality, cost-efficient public goods, services and facilities. The study indicated that there is a need to develop a common vision between both public and private entities that can be built using good governance, sound management, transparency, commitment and trust.…”
Section: Literature Review and Research Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…The study indicated that the extent and quality of voluntary information disclosed by the private construction companies was low. Samir and Maher (2018) analyzed the role of public private partnership in Egypt in terms of developing meaningful cooperation between the governments and private sector companies in a way that enables the provision of high-quality, cost-efficient public goods, services and facilities. The study indicated that there is a need to develop a common vision between both public and private entities that can be built using good governance, sound management, transparency, commitment and trust.…”
Section: Literature Review and Research Problemmentioning
confidence: 99%
“…The partnership between the public sector and private sector has two main drivers, the first of which is the financial driver that allows the public sector to make a capital investment without incurring any loans (Samir & Maher, 2018). In many countries, the PPP scheme has been developed primarily due to financial lack of provision of public infrastructure and public services.…”
Section: Background Of the Pppmentioning
confidence: 99%
See 3 more Smart Citations